Indonesian date with the single dad - Gilmore, Jessica (Billion dollar matches, 2021)
"Happy ever after...For the matchmaker? In this Billion-Dollar Matches story, when dating agency owner Madison Morgan flies out to Indonesia to tell billionaire single dad Luke Taylor that the match she'd arranged for him has fallen through, she never imagines she'll become his stand-in date! But as they sail through the Indian Ocean on a luxury yacht together and meet up with his little girl in Sydney, Madison's long-hidden yearning for a loving family comes hurtling back into view..."--Back cover.